Service differentiation in multihoming software defined vehicular networks - Nogueira, Miguel Gomes (2023)
Vehicular Ad-Hoc Networks are used by vehicles to communicate between them and with the road infrastructure, allowing users to enjoy a wide range of useful applications and services, like emergency services and alerts about the road and weather conditions, among others. However, the highly dynamic topology of these networks, the variability of the mobility patterns and the rapidly changing connectivity parameters, introduce several challenges to the operation and management of these infrastructures, namely challenges related to Quality of Service provisioning, connectivity, bandwidth and security assurance. Due to its flexible and adaptive control paradigm, Software Defined Networking emerged as the new solution that can cope with the highly dynamic nature of these communication infrastructures in a cost-effective way. By separating the forwarding and control planes, network management is simplified and a new flexibility is added to the network operation. This dissertation is focused on the development of additional features for an SDNbased Vehicular Ad-Hoc Network deployed in the Aveiro Tech City Living Lab with no support for service differentiation: at each moment, every On-Board Unit (OBU) forwards all traffic through the Road Side Unit (RSU) that presented the best coverage level. The main goal of this work is the implementation of support for UDP and TCP services differentiation in the existing infrastructure, thus developing Quality of Service features in the existing communication framework. Basically, if one OBU is located in the coverage area of several RSUs, it should decide which RSU will be used to forward each traffic flow based on its priority level. In the absence of any RSU, a cellular connection can be used to forward traffic from active services.